PENGARUH NARSISME CEO DAN ARUS KAS BEBAS TERHADAP KINERJA PERUSAHAAN - Nawang Kalbuana; Kusiyah Kusiyah; Rusdiyanto Rusdiyanto (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
Researchers are actively exploring how CEO narcissism affects CEO behavior in depth. The purpose of this study is to examine the relationship between CEO narcissism and the company's free cash flow to company performance. Quantitative research methods were used in this research with purposive sampling which produced as many as 110 samples from the most index companies in Jakarta Islamic Index from 2017 to 2021. Testing this study using the SPSS 26 application. The results of this study obtained empirical evidence that company performance is not influenced by the narcissistic behavior of narcissistic CEO. The company's performance is affected by the free cash flow available for investment. Simultaneously the narcissism of the CEO and free cash flow successfully affect the performance of the company.